2021
DOI: 10.3389/fnins.2021.765677
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Abnormalities of White Matter Microstructure in End-Stage Renal Disease Patients: An Automated Fiber Quantification Tractography Study

Abstract: Background and Purpose: End-stage renal disease (ESRD) results in extensive white matter abnormalities, but the specific damage segment cannot be identified. This study aimed to determine the segmental abnormalities of white matter microstructure in ESRD and its relationship with cognitive and renal function indicators.Methods: Eighteen ESRD patients and 19 healthy controls (HCs) were prospectively recruited. All participants underwent DTI and clinical assessments. Automatic fiber quantification (AFQ) was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…As frontal-temporal association fibers, previous studies indicated that they may be associated with symptoms of cognitive decline. [32][33][34] Studies focusing on neuropsychological impairments in WD have highlighted that patients with WD showing neurological signs present significant deficits in a wide range of cognitive domains. 35 The UF fiber links the anterior temporal lobe to the medial and lateral orbitofrontal cortex and plays a role in episodic memory, language, semantic activities, and social-emotional processing.…”
Section: Discussionmentioning
confidence: 99%
“…As frontal-temporal association fibers, previous studies indicated that they may be associated with symptoms of cognitive decline. [32][33][34] Studies focusing on neuropsychological impairments in WD have highlighted that patients with WD showing neurological signs present significant deficits in a wide range of cognitive domains. 35 The UF fiber links the anterior temporal lobe to the medial and lateral orbitofrontal cortex and plays a role in episodic memory, language, semantic activities, and social-emotional processing.…”
Section: Discussionmentioning
confidence: 99%
“…We also performed data format conversion, head motion eddy correction, gradient orientation correction, brain mask acquisition, and tensor calculation using the Functional MRI of the Brain Software Library version 6.0.3 commands to generate FA, MD, AD, RD, S0, and other files. 9,16,17…”
Section: Methodsmentioning
confidence: 99%
“…We also performed data format conversion, head motion eddy correction, gradient orientation correction, brain mask acquisition, and tensor calculation using the Functional MRI of the Brain Software Library version 6.0.3 commands to generate FA, MD, AD, RD, S0, and other files. 9,16,17 CST tracking and extraction were performed using the MATLAB platform and open-source AFQ software (https:// github.com/yeatmanlab/AFQ). The process mainly included (1) converting the data obtained from the previous steps into a dt6 file in MATLAB format using the dtiMakeDt-6FromFsl command; (2) setting the tracking parameters for FA threshold greater than 0.2 and turning angle less than 45° for whole-brain fiber tracking; (3) segmenting 20 major fiber tracts from whole-brain fibers; (4) cleaning up the raw fiber tracts based on the average length or 4 standard deviations of fiber bundle cores to clean up the original fiber bundles; (5) equally dividing the CST into 100 subsegments from the midbrain to the primary motor cortex and extracting diffusion tensor values for each segment; to comprehensively assess the microstructural changes in the CST during stroke rehabilitation, we computed the FA, MD, AD, and RD values for each subsegment, as these indexes provide distinct perspectives on fiber bundle damage 18 ; (6) to facilitate inter-group comparisons, the data of the subjects with right hemisphere cerebral infarction were flipped left-right; consequently, the left-side data of all patients represented the ipsilesional side, while the right-side data represented the contralesional side; correspondingly, accounting for the potential systematic effects from hemispheric differences, for the HC group, a new set of data, including bilateral corticospinal data, was generated after flipping the left and right hemispheres; and (7) extracting CST information, with the left CST being ipsilateral to the lesion and the right CST being contralateral to the lesion (Figure 1).…”
Section: Image Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Automated fiber-tract quantification (AFQ) is an advanced DTI method for automated reconstruction of WM fiber tracts and segmentation of the fiber tracts into multiple nodes. It can provide more detailed information on WM damage and has been applied to MCI, schizophrenia, cerebral small vessel disease, benign childhood epilepsy, end-stage renal disease, and so on (Sun et al, 2015;Chen et al, 2020;Jiang et al, 2021;Shu et al, 2021;Stone et al, 2021). To our knowledge, the application of AFQ for patients with NMOSD has not been studied.…”
Section: Introductionmentioning
confidence: 99%